Effect of pulse shaping on solidification process and crack in 5083 aluminum alloy by pulsed laser welding. (February 2021) - Jia, Zhiyuan; Zhang, Peilei; Yu, Zhishui; Shi, Haichuan; Liu, Hongbing; Wu, Di; Ye, Xin; Wang, Fuxin; Tian, Yingtao
Highlights: Ramp-down and step-down pulse shaping were designed to suppress 5083 aluminum alloy cracks. Ramp-down pulses decrease the volume of liquid molten pool at the end of the laser process. Tailing pulses increase the temperature gradient of the solidification process and reduce the vulnerable zone length. The effect of pulse shaping on crack suppression in vertical direction is more obvious than that in horizontal direction. Abstract: Solidification crack was a common welding defect in welding of aluminum alloy. When solidification shrinkage and heat shrinkage of the vulnerable zone and its surrounding solids were hindered, it will cause grain boundary cracking owing to insufficient supply of liquid metal. Therefore, cracks generally appear in the middle part of aluminum alloy welding spot at the late stage of solidification. Compared with continuous laser, pulsed laser could meet more precise heat input control and was widely used in aluminum alloy sheet welding. In this research, by designing different pulse shaping to improve the solidification condition of the 5083 aluminum alloy pulsed laser welding spot, the numerical simulation was used for analyzing the solidification rate and temperature gradient of molten pool. Application of ramp-down pulse decreased crack cross-sectional area from 420475 µm 2 to 0, and step-down pulse could also effectively control the crack radius. The results showed that effect of suppressing solidification crack on the horizontal direction of the welding spot was obvious to the vertical direction. Using ramp-down or step-down pulse shaping also reduced the volume of the liquid molten pool at the end of the laser process, which decreased the shrinkage stress at the late stage of solidification.